Effects of EGF-coated titanium surfaces on adhesion and metabolism of bisphosphonate-treated human keratinocytes and gingival fibroblasts - Pansani, Taisa Nogueira [UNESP] (2021)
Objective: To assess the effects of epidermal growth factor (EGF)–coated titanium (Ti) discs on the adhesion and metabolism of keratinocytes and gingival fibroblasts exposed to nitrogen-containing bisphosphonates. Materials and methods: Keratinocytes and fibroblasts were seeded (1 × 105 cells/disc) on Ti discs coated with EGF (100 nM). After 24 h, cells were exposed or not to sodium alendronate (SA) or zoledronic acid (ZA) at different concentrations (0 = control, 0.5, 1, or 5 μM) for 48 h. Cell adhesion to the substrates was evaluated by fluorescence microscopy. Cell viability (alamarBlue, n = 6) and synthesis of vascular endothelial growth factor (VEGF), matrix metalloproteinase-2 (MMP-2), and keratinocytes growth factor (KGF) (ELISA, n = 6) were assessed. Data were statistically analyzed by one-way ANOVA and Tukey tests (α = 0.05). Results: Higher cell adhesion rate was observed when keratinocytes and fibroblasts were seeded onto EGF-coated discs in comparison to uncoated discs. ZA treatment hindered the adhesion of both cell lines on the Ti discs as well as reduced the viability and synthesis of VEGF, KGF and MMP-2 by cells (p < 0.05). SA treatment did not affect cell viability, but interfered negatively on the adhesion and synthesis of EGF and KGF by the cells (p < 0.05). EGF-coated surface increased cell viability and synthesis of growth factors as well as downregulated the synthesis of MMP-2 in comparison to control (p < 0.05). Conclusion: EGF applied on Ti surface improves the biological responses of oral mucosa cells exposed to SA and ZA. Clinical relevance: EGF-coating on titanium may be a suitable strategy to improve oral mucosa cellular events related to biological sealing, especially for patients under bisphosphonate therapy.